Systematic investigation of sequence requirements for DNA i-motif formation - Školáková, Petra; Renčiuk, Daniel; Palacký, Jan; Krafčík, Daniel; Dvořáková, Zuzana; Kejnovská, Iva; Bednářová, Klára; Vorlíčková, Michaela (Nucleic acids research, 2019)
The formation of intercalated motifs (iMs) - secondary DNA structures based on hemiprotonated C.C+ pairs in suitable cytosine-rich DNA sequences, is reflected by typical changes in CD and UV absorption spectra. By means of spectroscopic methods, electrophoresis, chemical modifications and other procedures, we characterized iM formation and stability in sequences with different cytosine block lengths interrupted by various numbers and types of nucleotides. Particular attention was paid to the formation of iMs at pH conditions close to neutral. We identified the optimal conditions and minimal requirements for iM formation in DNA sequences, and addressed gaps and inaccurate data interpretations in existing studies to specify principles of iM formation and modes of their folding.
Keywords: Cytosine; DNA; koncentrace vodíkových iontů; sekvence nukleotidů; nukleotidové motivy; termodynamika; konformace nukleové kyseliny; kinetika; Base Sequence; Hydrogen-Ion Concentration; Nucleic Acid Conformation; Nucleotide Motifs; párování bází; Kinetics; cytosin; Base Pairing; Thermodynamics